Slaughter, Carcass and Non-Carcass Characteristics of Local Cattle and Buffalo in Indonesia - Priyanto, R.; Nuraini, H.; Muladno; Ismail, M.; Wijayanto, H. (Pakistan Journal of Nutrition, 2019)
Background and Objectives: Local cattle and buffalo slaughtered in public abattoirs vary widely in body fatness and live weight. The study was aimed to characterise carcass and non-carcass parameters of local cattle and buffalo differing in breed, sex and body fatness score using a carcass dressing procedure based on the national standard carcass definition. Methodology: A total of 291 cattle and buffalo were slaughtered at 20 public abattoirs from ten provinces of Indonesia. The slaughtered animals were classified according to breed (Bali, Madura, PO, local crossbred cattle, PFH and buffalo), body fatness score (very thin, thin, medium, fat and very fat) and sex (male and female). Results: The results indicated that the local cattle and buffalo slaughtered at public abattoirs were dominated by local crossbred cattle (59%), followed by Bali cattle (14%), PFH cattle (10%), PO cattle (8%), Madura cattle (7%) and swamp buffalo (2%). The animals were mainly in medium (49%) and poor (36%) conditions, while only 15% of the animals were in fat condition. Variations due to breed, age, sex and body fatness score were observed in slaughter weight, carcass and non-carcass characteristics. Conclusion: Overall, the majority of local cattle and buffalo of various breeds, ages and sexes slaughtered at public abattoirs in Indonesia had low to medium carcass productivity, which could be improved by increasing their body fatness score.